Penggunaan Corong Berhitung Untuk Meningkatkan Kemampuan Operasi Hitung Penjumlahan Pada Murid Tunanetra Kelas Dasar II DI SLB Soppeng - Syamsuddin Syamsuddin; Triyanto Pristiwaluyo; Andi Budiman (Seminar Nasional LP2M UNM, 2019)
This study examines the low learning outcomes of blind students in mathematics, especially recognizing the arithmetic operations of students with visual impairments in SLB Soppeng. The formulation of the problem in this study is "Does the use of a counting funnel can improve the ability to calculate the number of students in blind class II in SLB Soppeng". The purpose of this study is 1) To find out the total count operations on blind students of Class II in SLB Soppeng in the analysis under conditions of baseline 1 (A1), 2) To find out the count operations on blind students of Class II in the Soppeng SLB in the analysis in intervention conditions (B), 3) to find out the total count operations in blind students in Class II in SLB Soppeng in the analysis under the baseline conditions 2 (A2), 4) to determine the increase in the ability to count operations through counting funnels based on the results of the analysis between conditions from baseline 1 (A1) to intervention (B) and from intervention (B) to baseline 2 (A2) in blind class II blind children in Soppeng SLB. Data collection techniques used were performance tests. The subjects in this study were 1 elementary class II blind student in Soppeng SLB with the initials AF. This study uses an experimental method using Single Subject Research (SSR) with A-B-A design. By using the counting funnel can increase the ability to calculate the number of operations on blind students. The data obtained were analyzed through descriptive statistics and displayed in the form of percentages, graphs and means. The results of the study concluded that the use of a counting funnel can improve the ability to calculate the number of students with visual grade II blindness in SLB Soppeng.